ANALYSIS OF THE QUALITY OF PUBLIC SERVICES IN THE UPTD SECTION, KUTA SELATAN DISTRICT REGIONAL REVENUE AGENCY BADUNG REGENCY - Adistya Chandra, Dwi; Eviani Yuliantari, I Gusti Ayu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Public service involves a very broad aspect of life. In the life of the state, the government has the function of providing various public services needed by the community, ranging from services in the form of regulation or other services to meeting the needs of the community in the fields of education, health, utilities, and others. Service quality plays an important role to achieve the level of customer satisfaction. The image of good service quality becomes the government's point of view or perception but is based on the customer's point of view. Inside the Pasedahan Agung Regional Revenue Agency, Badung Regency at the UPTD, South Kuta District, there is a problem with the quality of public service analysis where administrative services are one form of public service that provides services. to serve and produce the required official documents. Talking about the form of documents, there are many types of, ranging from land ownership documents, citizenship, competency certification, and many more such as KTP, BPKB, STNK, IMB, and SIM. application development thus requiring people to come to take care of online administration. Based on the discussion above, it can be said that this problem can be overcome if the principles of public service are by the procedures and the application of application development applications that make it easier for people to use services in this digital era.